Review of 1974/02/02 Concert at Royal Northern College of Music, Manchester. Music Digest: The Music of Edgard Varèse. Saar Radio Symphony Orchestra conducted by Hans Zender, Stephen Roberts (bass) - Smalley, Denis (Contact: A Journal for Contemporary Music (1971-1990), 2019)